Curable fluoropolymer compositions comprising an ammonium hydrobenzate catalyst and a bishphonitrile-containing compound

By using highly fluorinated amorphous polymers with high nitrile group content and curing with ammonium hydroxybenzoate catalyst and diphthalene additives, the problem of poor anti-compression and permanent deformation performance of fluorinated elastomers at extreme temperatures is solved, and excellent performance at high temperatures is achieved.

CN119546692APending Publication Date: 2025-02-283M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052900.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-06-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Under extreme temperature conditions, the compression-resistant permanent deformation properties of fluorine-containing elastomers are difficult to maintain, especially at temperatures of 275°C or above.

Method used

A highly fluorinated amorphous polymer containing nitrile groups was used and cured by an ammonium hydroxybenzoate catalyst and a diphthalene-containing additive to form an elastomer with excellent high temperature characteristics.

Benefits of technology

It achieves good compression permanent deformation performance under high temperature conditions (such as 300℃, 325℃ or 335℃), and improves the stability and performance of the material at extreme temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235290780000011
    Figure BDA0005235290780000011
  • Figure BDA0005235290780000021
    Figure BDA0005235290780000021
  • Figure BDA0005235290780000022
    Figure BDA0005235290780000022
Patent Text Reader

Abstract

Described herein are fluoropolymer compositions comprising an ammonium hydroxybenzoate catalyst and a bisphthalonitrile-containing compound. As disclosed herein, by curing a highly fluorinated amorphous fluoropolymer using an ammonium hydroxybenzoate catalyst and a bisphthalonitrile-containing compound, highly fluorinated elastomers with low compression set at temperatures above 300 DEG C can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to curable fluoroelastomer compositions containing compounds having ammonium hydroxybenzoate catalysts and additives containing two phthalonitrile groups. The use of such compounds to cure amorphous fluoropolymers containing nitrile cure site groups and the cured compositions are also described. Summary of the invention

[0002] Compression set resistance is the ability of a material to recover to its original thickness after being compressed under a load for a certain period of time at a given temperature. When highly fluorinated elastomers are tested for compression set resistance at elevated temperatures, the temperature is typically 275°C or even 300°C. However, in some applications, fluoroelastomers are used under extreme temperature conditions (e.g., at least 325°C, 330°C, or even 335°C). Therefore, there is a need to identify compositions that exhibit good compression set when subjected to extreme temperatures.

[0003] In one aspect, a composition is described comprising (i) an uncured highly fluorinated amorphous polymer comprising nitrile groups, wherein at least 80 mol % of the hydrogen atoms of the polymer backbone of the highly fluorinated amorphous polymer have been substituted with fluorine atoms, and (ii) an ammonium hydroxybenzoate compound according to the formula:

[0004]

[0005] wherein each R1 group is independently selected from the group consisting of: H, OH, R and OR, provided that at least one R1 group is OH, and wherein R is an alkyl group; and

[0006] (iii) Additives according to formula (II)

[0007]

[0008] Where X 1 and X 2 is independently selected from O or S, and L comprises at least one multivalent six-membered aromatic hydrocarbon group.

[0009] In another aspect, an article is described. An article comprising a cured elastomer derived from a composition comprising (i) an uncured highly fluorinated amorphous polymer comprising nitrile groups, wherein at least 80 mol % of the hydrogen atoms of the polymer backbone of the highly fluorinated amorphous polymer have been substituted with fluorine atoms, and (ii) an ammonium hydroxybenzoate compound according to the formula:

[0010]

[0011] wherein each R1 group is independently selected from the group consisting of: H, OH, R and OR, provided that at least one R1 group is OH, and wherein R is an alkyl group, preferably a C1 to C4 alkyl group; and

[0012] (iii) Additives according to formula (II)

[0013]

[0014] Where X 1 and X 2 is independently selected from O or S, and L comprises at least one multivalent six-membered aromatic hydrocarbon group.

[0015] In another aspect, the use of an ammonium hydroxybenzoate compound according to the following formula (I) and an additive according to formula (II) for curing an uncured highly fluorinated amorphous polymer containing nitrile groups is described.

[0016]

[0017] wherein each R1 group is independently selected from the group consisting of: H, OH, R, and OR, provided that at least one R1 group is OH, and wherein R is an alkyl group;

[0018]

[0019] Where X 1 and X 2 is independently selected from O or S, and L comprises at least one multivalent six-membered aromatic hydrocarbon group, wherein at least 80 mol % of the hydrogen atoms of the polymer backbone of the highly fluorinated amorphous polymer have been substituted with fluorine atoms.

[0020] The above summary of the invention is not intended to describe every embodiment. The details of one or more embodiments of the present invention are also listed in the following detailed description. Other features, objectives and advantages will be apparent from this specification and claims. DETAILED DESCRIPTION

[0021] As used herein, the term

[0022] "A", "an" and "the" are used interchangeably and refer to one or more; and

[0023] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B);

[0024] "Backbone" means the main continuous chain of a polymer;

[0025] “Cross-linking” refers to the use of chemical bonds or chemical groups to connect two preformed polymer chains;

[0026] “Cure sites” refer to functional groups that can participate in cross-linking;

[0027] "Interpolymerization" means polymerizing monomers together to form a polymer backbone;

[0028] A "monomer" is a molecule that can be polymerized and then form the basic structural part of a polymer;

[0029] "Perfluorinated" means a group or compound derived from hydrocarbons in which all hydrogen atoms are replaced by fluorine atoms. However, perfluorinated compounds may also contain other atoms besides fluorine and carbon atoms, such as oxygen, chlorine, bromine and iodine atoms; and

[0030] "Polymer" refers to a macrostructure having a number average molecular weight (Mn) of at least 30,000 Daltons, at least 50,000 Daltons, at least 100,000 Daltons, at least 300,000 Daltons, at least 500,000 Daltons, at least 750,000 Daltons, at least 1,000,000 Daltons, or even at least 1,500,000 Daltons, and the molecular weight is not so high as to cause premature gelation of the polymer.

[0031] As used herein, and as known in the art, such structures The horizontal line intersecting the benzene ring shown in represents a bond connected to any one of the vertices of the ring.

[0032] Also herein, ranges recited by endpoints include all numbers subsumed within that range (eg, 1 to 10 includes 1.4, 1.9, 2.33, 5.75, 9.98, etc.).

[0033] Moreover, as used herein, the expression "at least one" includes all numbers from one to greater than one (eg, at least 2, at least 4, at least 6, at least 8, at least 10, at least 25, at least 50, at least 100, etc.).

[0034] As used herein, "comprising at least one of A, B, and C" means comprising only element A, only element B, only element C, A and B, A and C, B and C, and a combination of all three.

[0035] The present disclosure relates to the use of a non-fluorinated cure package comprising a diphthalonitrile-containing compound and an ammonium hydroxybenzoate catalyst to cure a highly fluorinated amorphous fluoropolymer containing nitrile cure sites. The resulting cured highly fluorinated elastomer has been found to have excellent high temperature properties (e.g., improved compression set at high temperatures).

[0036] Fluoropolymers

[0037] As used herein, a "highly fluorinated" polymer is one in which at least 80 mol % (e.g., at least 90 mol % or even at least 95 mol %) of the hydrogen atoms of the polymer backbone have been replaced with fluorine atoms. In some embodiments, 0 to 20 mol % (e.g., 5 to 15 mol %) of the hydrogen atoms of the polymer backbone may be replaced with chlorine atoms. In some embodiments, these highly fluorinated polymers may include one or more hydrogen-containing end or side groups that are not considered part of the polymer backbone.

[0038] In some embodiments, the highly fluorinated fluoropolymer is a copolymer of tetrafluoroethylene (TFE) and one or more perfluorinated comonomers. In some embodiments, at least one perfluorinated comonomer is a perfluoroalkyl vinyl ether (PAVE), including perfluoroalkyl alkoxy vinyl ether. Suitable PAVE includes perfluoromethyl vinyl ether (PMVE), perfluoroethyl vinyl ether (PEVE) and perfluoropropyl vinyl ether (PPVE-1 and PPVE-2). In some embodiments, at least one perfluorinated comonomer is a perfluoroalkyl allyl ether (PAAE), including perfluoroalkyl alkoxy allyl ether. Suitable PAAE includes perfluoromethyl allyl ether (MA-1), perfluoroethyl allyl ether (MA-2) and perfluoropropyl allyl ether (MA-3).

[0039] In some embodiments, at least one perfluorinated comonomer is a perfluorinated α-olefin other than TFE, such as hexafluoropropylene (HFP). Additional optional comonomers include partially fluorinated α-olefins (e.g., CH2=CF2, VDF); olefins containing F and Cl, such as chlorotrifluoroethylene; and non-fluorinated α-olefins, such as ethylene or propylene.

[0040] In some embodiments, the fluoropolymer is perfluorinated, i.e., at least 99 mol % or even 100 mol % of the hydrogen atoms of the polymer backbone have been replaced by fluorine atoms or chlorine atoms (preferably fluorine atoms). If chlorine atoms are present, they account for no more than 20 mol %, e.g., no more than 10 mol %, based on the total moles of fluorine atoms and chlorine atoms on the polymer backbone. In some embodiments, the perfluorinated polymer comprises no more than 5 mol % (e.g., no more than 1 mol % or even no more than 0.01 mol %) of chlorine atoms, based on the total moles of fluorine atoms and chlorine atoms on the polymer backbone.

[0041] Typically, highly fluorinated fluoropolymers contain a sufficient number of nitrile groups (C≡N) to achieve the desired degree of curing (i.e., crosslinking). In some embodiments, the fluoropolymer contains at least 0.1 mol % of nitrile groups, such as at least 0.5 mol % or even at least 1 mol % of nitrile groups. In some embodiments, the fluoropolymer contains no more than 5 mol %, such as no more than 2 mol % or even no more than 1.5 mol % of nitrile groups.

[0042] In some embodiments, nitrile groups are introduced by copolymerizing nitrile-containing cure site monomers with other comonomers (e.g., TFE, PAVE, and PAAE comonomers). Examples of nitrile-containing cure site monomers correspond to the following formulas: CF2=CF-CF2-O-Rf-CN; CF2=CFO(CF2) r CN; CF2 = CF[OCF2CF(CF3)] k O(CF2) u CN; and CF2 = CFO [CF2CF (CF3) O] p (CF2) v OCF(CF3)CN, wherein r represents an integer from 2 to 12; p represents an integer from 0 to 4; k represents 1 or 2; v represents an integer from 0 to 6; u represents an integer from 1 to 6, and Rf is a perfluoroalkylene group or a divalent perfluoroether group. Specific examples of nitrile-containing fluorinated monomers include, but are not limited to, CF2=CFOCF2CF(CF3)OCF2CF2CN, CF2=CFOCF2(CF2)3CF2CN(MV5CN), and CF2=CFOCF2(CF2)3CF(CF3)CN.

[0043] If the amorphous fluoropolymer is perfluorinated, then typically at least 50 mol% (mol%) of its interpolymerized units are derived from TFE, optionally including HFP. The remainder of the interpolymerized units of the amorphous fluoropolymer (e.g., 10 mol% to 50 mol%) is composed of one or more perfluorinated vinyl ethers or perfluorinated allyl ethers as described above in its embodiments and a curing site monomer as described above in its embodiments. In some embodiments, the molar ratio of the unit derived from the TFE comonomer unit to the comonomer unit derived from the above-mentioned perfluorinated vinyl ether or perfluorinated allyl ether can be, for example, 1:1 to 4:1, wherein the unsaturated ether can be used as a single compound or as a combination of two or more unsaturated ethers. A typical composition comprises 44 wt% to 62 wt% of TFE and 38 wt% to 56 wt% of PMVE and 0.1 wt% to 10 wt% of curing site monomers and 0 wt% to 10 wt% of other comonomers or modifiers, wherein the amount of each component is selected so that the total amount is 100 wt%.

[0044] If the amorphous fluoropolymer is not perfluorinated, it generally contains about 5 mol% to about 90 mol% of its interpolymerized units derived from TFE, CTFE and / or HFP; about 5 mol% to about 90 mol% of its interpolymerized units derived from VDF, ethylene and / or propylene; up to about 40 mol% of its interpolymerized units derived from perfluorinated vinyl ethers or perfluorinated allyl ethers as described above in any embodiment thereof; and about 0.1 mol% to about 5 mol%, in some embodiments, about 0.3 mol% to about 2 mol% of cure site monomers. Some typical compositions contain about 22 wt% to 30 wt% TFE, 30 wt% to 38 wt% VDF, 34 wt% to 42 wt% HFP, and 0.1 wt% to 10 wt% of cure site monomers and 0 wt% to 10 wt% of other comonomers or modifiers, wherein the amount of each ingredient is selected so that the total amount is 100 wt%.

[0045] Examples of amorphous perfluoropolymers that can be used in the present disclosure include TFE / perfluoromethyl vinyl ether (PMVE) copolymers, TFE / perfluoromethyl allyl ether (PMAE) copolymers, TFE / CF2=CFOC3F7 copolymers, TFE / CF2=CFCF2OC3F7 copolymers, TFE / CF2=CFOCF3 / CF2=CFOC3F7 copolymers, TFE / CF2=CFCF2OCF3 / CF2=CFCF2OC3F7 copolymers and TFE / HFP copolymers. In some embodiments, amorphous fluoropolymers useful in the present disclosure include TFE / propylene copolymers, TFE / propylene / VDF copolymers, VDF / HFP copolymers, TFE / VDF / HFP copolymers, TFE / ethyl vinyl ether (EVE) copolymers, TFE / butyl vinyl ether (BVE) copolymers, TFE / EVE / BVE copolymers, VDF / CF2=CFOC3F7 copolymers, ethylene / HFP copolymers, CTFE / VDF copolymers, TFE / VDF copolymers, TFE / VDF copolymers, TFE / VDF / PMVE / ethylene copolymers, and TFE / VDF / CF2=CFO(CF2)3OCF3 copolymers. Each of the foregoing copolymers will contain monomer units having cure sites.

[0046] Ammonium Hydroxybenzoate Catalyst

[0047] The catalyst of the present disclosure is an ammonium hydroxybenzoate compound. As used herein, a hydroxybenzoate is a benzoate derivative substituted with one or more hydroxyl groups at any position on the benzene ring, as shown in formula (I):

[0048]

[0049] wherein at least one R1 is OH. In some embodiments, each R1 is independently H or OH. In some embodiments, one or more R1 groups may be an alkyl group or an alkoxy group, such as a C1 to C4 alkyl or alkoxy group.

[0050] In one embodiment, only one R1 group is OH. For example, in one embodiment, the hydroxybenzoic acid ammonium compound is

[0051]

[0052] wherein each R1 group is independently selected from the group consisting of: H, R and OR, wherein each R is independently selected from an alkyl or alkoxy group having 1, 2, 3 or 4 carbon atoms. In one embodiment, each R1 group is H.

[0053] In another embodiment, the ammonium hydroxybenzoate compound is

[0054]

[0055] wherein each R1 group is H, and R3 is a C1 to C4 alkyl group.

[0056] In another embodiment, the ammonium hydroxybenzoate compound is

[0057]

[0058] wherein each R1 group is H.

[0059] In some embodiments, the anion can be a monohydroxybenzoate, such as an anion of 2-hydroxybenzoic acid (also known as salicylic acid) or 4-hydroxybenzoic acid. In some embodiments, the benzoate anion can be substituted by two or more hydroxyl groups. For example, in some embodiments, the anion can be a trihydroxybenzoate, such as an anion of 3,4,5-trihydroxybenzoic acid (also known as gallic acid). In some embodiments, the anion can include one or more substituents other than the hydroxyl group. For example, in some embodiments, the anion can be a hydroxy-alkyl or hydroxy-alkoxybenzoate, such as an anion of 4-hydroxy-3-methoxybenzoic acid (also known as vanillic acid).

[0060] Typically, ammonium benzoate is commercially available. However, such compounds can also be formed by reacting the corresponding benzoic acid compound with NH3, for example according to the following reaction:

[0061]

[0062] Such reactions are known in the art. For example, the benzoic acid form of the compound can be dissolved in a minimum amount of ethanol at room temperature. In a separate flask, an ammonium hydroxide solution (25-30 wt % ammonium hydroxide) is gently heated to produce ammonia vapor, which is then bubbled through the benzoic acid solution. Ammonia is continued to be added until further heating from the exothermic reaction stops. During the reaction, ammonium benzoate precipitates from the solution. After the reaction is complete, the product can be vacuum filtered and rinsed with acetone. The remaining solvent can be removed in a vacuum with a rotary evaporator.

[0063] Compounds containing diphthalonitrile

[0064] The bisphthalonitrile-containing compounds of the present disclosure are according to formula (II):

[0065]

[0066] Where X 1 and X 2 are independently selected from O or S, and L comprises at least one polyvalent aromatic hydrocarbon group. 1 -LX 2 The group is bonded to the ortho or meta position of a nitrile group in the nitrile (-C≡N) group. L is a polyvalent linking group comprising at least one polyvalent aromatic hydrocarbon group. L may comprise one or more hexavalent aromatic hydrocarbon groups. In one embodiment, L comprises a polyvalent fused polycyclic portion. The polyvalent linking group L may be divalent, trivalent or tetravalent.

[0067] In one embodiment, L is

[0068]

[0069] The two horizontal lines represent (i) a vertex of the 6-membered aromatic ring and X 1 The bonds between (ii) different vertices of the aromatic ring and X 2 The two bonds can be ortho, meta or para to each other. 1 Between the aromatic ring and X 2 In addition to the two bonds between the aromatic hydrocarbon groups, there may be other non-functional groups that do not cause steric hindrance, such as at least one methyl group, methoxy group, ethyl group and / or ethoxy group, bonded to the aromatic hydrocarbon group.

[0070] In one embodiment, L is phenylene or substituted phenylene. For example, in one embodiment, L is

[0071]

[0072] The two horizontal lines in each structure represent (i) the connection between a vertex of the aromatic ring and X1 and (ii) different vertices of the aromatic ring and X 2 The two bonds may be ortho, meta or para to each other. In addition to the two bonds, there may be other non-functional groups bonded to the aromatic ring, such as those indicated by R above. 1 and R 2 As shown, these non-functional groups do not cause steric hindrance, and such non-functional groups include short-chain (e.g., containing 1, 2, 3 or 4 carbon atoms) alkyl groups and alkoxy groups. Exemplary R 1 Group and R 2 The groups include: methyl group, methoxy group, ethyl group and ethoxy group.

[0073] In another embodiment, L comprises more than one aromatic group, such as naphthalene, anthracene, phenanthrene, or a divalent group having the structure:

[0074] as well as

[0075] Where R 4 is selected from the group consisting of: a bond, -S-, -O-, -C(CF3)2-, -C(CH3)2-, -CH2-, -SO2-, -C(=O)-, and -C(CH3)2-C6H4-C(CH3)2-. In the above structure of L, L and X of the compound containing diphthalonitrile are connected. 1 and X 2 The bond can be located relative to R 4 For example, with X 1 and X 2 The bonds can be independently R 4 More preferably, with X 1 and X 2 The bond relative to R 4 The groups are all ortho, all meta or all para. 1 Between phenylene and R 4 In addition to the two bonds between the phenylene groups, there may be other non-functional groups bonded to the phenylene groups that do not cause steric hindrance, such as at least one methyl group, methoxy group, ethyl group and / or ethoxy group. 1 Group and R 2 The groups include: methyl group, methoxy group, ethyl group and ethoxy group.

[0076] In one embodiment, L comprises a fused polyaryl ring such as naphthalene, anthracene, phenanthrene or

[0077] Exemplary compounds of formula (II) include:

[0078]

[0079] Curable composition

[0080] The ammonium hydroxybenzoate catalyst according to formula (I) and the bisphthalonitrile-containing compound of formula (II) can be used to cure highly fluorinated nitrile-group-containing amorphous fluoropolymers.

[0081] In one embodiment, at least 0.05, 0.1 or even 1 part by weight, and at most 2, 4, 6 or even 10 parts by weight of ammonium hydroxybenzoate catalyst are used per 100 grams of amorphous highly fluorinated polymer. In one embodiment, at least 0.05, 0.1 or even 1 part by weight, and at most 2, 2.5, 3, 4, 5, 6, 8 or even 10 parts by weight of a compound containing bisphthalonitrile according to formula (II) are used per 100 grams of amorphous highly fluorinated polymer.

[0082] In some embodiments, the curable composition comprising a highly fluorinated nitrile-group-containing amorphous fluoropolymer, an ammonium hydroxybenzoate catalyst according to formula (I), and a diphthalonitrile-containing compound of formula (II) may also contain various types of additives commonly used in the preparation of elastomeric compositions, such as acid acceptors, processing aids, pigments, fillers, pore formers, and those additives known in the art.

[0083] Such fillers include: organic or inorganic fillers, such as clay, silica (SiO2), alumina, red iron, talc, diatomaceous earth, barium sulfate, wollastonite (CaSiO3), calcium carbonate (CaCO3), calcium fluoride, titanium oxide, iron oxide and carbon black fillers, polytetrafluoroethylene powder, fluorinated plastics such as polytetrafluoroethylene, PFA (TFE / perfluorovinyl ether copolymer) powder, conductive fillers, heat dissipation fillers, etc. can be added to the composition as optional components. Those skilled in the art are able to select the desired amount of specific fillers to achieve the desired physical properties of the vulcanized compound. The filler component can produce a compound that can maintain the preferred elasticity and physical tension (as indicated by the elongation and tensile strength values) while maintaining the desired properties such as shrinkage at a lower temperature (TR-10).

[0084] In one embodiment, the composition comprises less than 50%, 40%, 30%, 20%, 15% or even 10% by weight of inorganic filler.

[0085] Conventional adjuvants may also be incorporated into the compositions of the present disclosure to enhance the properties of the resulting compositions. For example, acid acceptors may be used to promote the curing stability and thermal stability of the compound. Suitable acid acceptors may include magnesium oxide, lead oxide, calcium oxide, calcium hydroxide, lead hydrogen phosphite, zinc oxide, barium carbonate, strontium hydroxide, calcium carbonate, hydrotalcite, alkaline stearate, magnesium oxalate or a combination thereof. Acid acceptors are preferably used in an amount in the range of about 1 part to about 20 parts per 100 parts by weight of polymer.

[0086] Typically, the ammonium hydroxybenzoate catalyst, the diphthalonitrile-containing compound, and optional additives can be blended with a highly fluorinated amorphous fluoropolymer and formed into articles such as sheets and O-rings using commonly known equipment and methods. For example, the compounded composition can be press-cured at a temperature of at least 175°C (e.g., at least 185°C). In some embodiments, the press-curing temperature does not exceed 225°C or even does not exceed 200°C. The degree of cure can be determined according to the curing rheology test described in the examples. The press-curing time is selected to achieve the desired level of cure, which can be determined by the temperature of the M H Typically, sufficient curing is indicated by the H The curing time is preferably not more than 0.5, such as not more than 0.2, or even not more than 0.1, as measured according to the Curing Rheology Test described below. For most applications, t'90 (as measured according to the Curing Rheology Test) should be less than 20 minutes, such as not more than 10 minutes. In order to minimize the risk of scorch, t'90 should be at least 2 minutes. In some embodiments, longer curing times (e.g., t'90 values ​​of at least 4 minutes) may be beneficial.

[0087] Ideally, the molded mixture or pressurized cured article (e.g., in an oven) is post-cured at a temperature and time sufficient to complete the curing. Post-curing is usually between about 150°C and about 300°C, typically at about 230°C, for about 2 hours to 50 hours or longer, usually increasing with the cross-sectional thickness of the article. For thick sections, the temperature during post-curing is usually gradually increased from the lower limit of the range to the desired maximum temperature. The maximum temperature used is usually about 300°C, and the temperature is maintained for about 4 hours or more. The post-curing step usually completes cross-linking, and residual volatiles can also be released from the cured composition. In one embodiment, post-curing involves exposing the molded parts to non-isothermal thermal cycles. For example, the temperature is increased from room temperature to 150°C in 2 hours and maintained at 150°C for 7 hours, then raised to 300°C in 2 hours and maintained at 300°C for 2 hours. Finally, the part is raised to 320°C over 15 minutes and held for 15 minutes, then returned to ambient temperature (e.g., by turning off the oven heat). Another example of a suitable post-cure cycle involves exposing the molded part to heat under nitrogen using six stages of conditions. First, the temperature is increased from 25°C to 200°C over a period of 6 hours, then the part is held at 200°C for 16 hours, after which the temperature is increased from 200°C to 250°C over a period of 2 hours. The part is then held at 250°C for 8 hours, after which the temperature is increased from 250°C to 300°C over a period of 2 hours. The part is then held at 300°C for 16 hours. Finally, the part is returned to ambient temperature by, for example, turning off the oven heat.

[0088] In some applications, such as O-rings and seals, compression set is a key property. In some embodiments, the cured compositions of the present disclosure have improved compression set, especially at higher temperatures, such as at 300°C, 325°C, 335°C, or even 350°C. In some embodiments, the cured compositions have a compression set of no more than 60%, 55%, 50%, 40%, 35%, 30%, or even 25% after 70 hours at 300°C, as measured according to ASTM D 395-03 Method B and ASTM D 1414-94 at an initial deflection of 25%. In some embodiments, the cured compositions have a compression set of no more than 80%, 70%, 60%, 55%, 50%, or even 45% after 70 hours at 335°C, as measured according to ASTM D 395-03 Method B and ASTM D 1414-94 at an initial deflection of 25%. In some embodiments, the compositions of the present disclosure maintain article integrity when exposed to elevated temperatures.

[0089] Example

[0090] Unless otherwise indicated, all parts, percentages, ratios, etc. in the examples and the rest of the specification are by weight, and all materials are commercially available, for example, from Sigma-Aldrich Chemical Company, Milwaukee, WI, USA, or are known to those skilled in the art, unless otherwise indicated or obvious not to be the case.

[0091] The following abbreviations are used in this section: g = gram, cm = centimeter, min = minute, h = hour, N = Newton, dN·m = decinewton meter, °C = degrees Celsius, mol = mole, mol% = mole percent, mL = milliliter, NMR = nuclear magnetic resonance. Abbreviations of materials used in this section and descriptions of the materials are provided in Table 1.

[0092] Table 1 .

[0093]

[0094] Preparation Example 1: Additive A

[0095] 50.0 g (0.289 mol) of 4-nitrophthalonitrile, 48.55 g (0.144 mol) of 4,4'-(hexafluoroisopropylidene) diphenol, 49.9 g (0.361 mol) of anhydrous K2CO3 and 225 g of dry dimethyl sulfoxide (DMSO) were added to a three-necked 500 mL reaction flask. The reaction solution was heated to 70 ° C and mechanically stirred with bubbling nitrogen for 3.5 h. Stirring was stopped and the reaction salt was settled to the bottom of the container. Some reaction products have begun to crystallize from the reaction liquid. The reaction solution liquid and product were decanted from the reaction salt into a stirred and cooled mixture of 250 g 80 / 20 methanol / water (by mass). Additional products were crystallized from the DMSO / methanol / water solution. The reaction salt was washed with 25 g DMSO and the washed DMSO was decanted into a stirred DMSO / methanol / water solution. The product solids were collected on a Buchner funnel and washed with methanol, water and methanol. The solids were collected in an aluminum pan and dried in a convection oven at 140 ° C to remove methanol and water for 2h. The solid was further heated to 250 ° C for 15 min, which melted the solid and discharged residual DMSO. The product melt was taken out of the oven and cooled to ambient temperature. The product 79.0g (92.9% yield) had a melt temperature of 231 ° C-232 ° C by differential scanning calorimetry (DSC Q 2000, TA Instruments, New Castle, DE, New Castle, DE). The product was identified as bis(3,4-dicyanophenyl) ether of 4,4'-(hexafluoroisopropylidene) diphenol by infrared analysis and nuclear magnetic resonance (NMR) spectroscopy, and had a purity of> 99%.

[0096] Preparation Example 2: Additive B

[0097] 4-nitrophthalonitrile (48.8g) and 4,4'-biphenylene glycol (26.24g) are added to a two-necked 500mL round-bottomed flask. 200g of dimethylformamide (DMF) is added to the flask. By stirring on a magnetic stirring plate with an egg-shaped stirring bar, 4-nitrophthalonitrile and 4,4'-biphenylene glycol are dissolved in DMF. DBU (53.6g) is added once. The flask neck is sealed with a rubber septum, and a hot probe is inserted through a rubber septum. The solution is stirred with an egg-shaped stirring bar and heated to 70°C with a heating mantle. The flask solution is kept at 70°C for 2h. The solution is allowed to cool to ambient temperature. The product is precipitated by being added to 500mL of stirred methanol. The precipitate is collected under suction on a Buchner funnel with #4Whatman filter paper, and washed with 200mL of methanol, 200mL of water and 200mL of methanol. The collected solids were air dried overnight and further dried in a vacuum oven at 180° C. for 1 hour the next day. The solids 59.1 g (95.6% yield) had a melt temperature of 236° C. as measured by differential scanning calorimetry and were identified as 4,4′-bis(3,4-dicyanophenoxy)biphenyl by infrared and NMR analysis.

[0098] Preparation Example 3: Additive C

[0099] 50.0 g (0.289 mol) of 4-nitrophthalonitrile, 15.90 g (0.144 mol) of resorcinol, 49.9 g (0.361 mol) of anhydrous K2CO3 and 175 g of dry DMSO were added to a three-necked 500 mL reaction flask. The reaction solution was heated to 70 ° C and mechanically stirred for 3.5 h with bubbling nitrogen. Stirring was stopped and the reaction salt was settled to the bottom of the container. The reaction solution liquid and product were decanted from the reaction salt into a stirred and cooled mixture of 200 g 80 / 20 methanol / water (by mass). The product was crystallized from the DMSO / methanol / water solution. The reaction salt was washed with 25 g of DMSO and the washed DMSO was decanted into a stirred DMSO / methanol / water solution. The product solid was collected on a Buchner funnel and washed with methanol, water and methanol. The solid was collected in an aluminum pan and dried in a convection oven at 140 ° C to remove methanol and water for 2 h. The solid was further heated to 200°C in a vacuum oven for 1 h, which melted the solid and stripped off the residual DMSO. The product melt was removed from the oven and allowed to cool to ambient temperature. The product 47.3 g (90.4% yield) had a melt temperature of 185°C as measured by differential scanning calorimetry on a TA Instruments DSC Q 2000. The product was identified as bis(3,4-dicyanophenyl)ether of resorcinol by infrared analysis and NMR, and had a purity of>99%.

[0100] Preparation Example 4: Additive D

[0101] 50.0 g (0.289 mol) of 4-nitrophthalonitrile, 31.52 g (0.144 mol) of bisphenol T, 49.9 g (0.361 mol) of anhydrous K2CO3 and 225 g of dry DMSO were added to a three-necked 500 mL reaction flask. The reaction solution was heated to 70°C and mechanically stirred for 3.5 h with bubbling nitrogen. Stirring was stopped and the reaction salt was settled to the bottom of the container. The reaction solution liquid and product were decanted from the reaction salt into a stirred and cooled mixture of 250 g 80 / 20 methanol / water (by mass). The product was crystallized from the DMSO / methanol / water solution. The reaction salt was washed with 25 g DMSO and the washed DMSO was decanted into a stirred DMSO / methanol / water solution. The product solid was collected on a Buchner funnel and washed with methanol, water and methanol. The solid was collected in an aluminum pan and dried in a convection oven at 140°C to remove methanol and water for 2 h. The solid was further heated to 200°C in a vacuum oven for 1 h, which melted the solid and stripped off residual DMSO. The product melt was removed from the oven and allowed to cool to ambient temperature. The product 60.6 g (89.2% yield) had a melt temperature of 178°C as measured by differential scanning calorimetry on a TA Instruments DSC Q 2000. The product was identified as bis(3,4-dicyanophenyl)ether of bisphenol T by infrared analysis and NMR, and had a purity of >99%.

[0102] Samples were prepared in 100 g polymer batches by compounding on a two-roll mill the materials in the amounts listed in Table 2. For example, 0.75 g of catalyst was added to 100 g of fluoropolymer A in CE-1.

[0103] Curing rheology testing was performed using uncured, compounded samples using a rheometer available from Alpha technologies, Hudson, OH under the trade designation PPA 2000, according to ASTM D 5289-93a at 177°C, no preheat, 15 minutes elapsed time, and 0.5 degrees arc. The plateau or maximum torque (M) was not reached. H ) is the minimum torque (M) obtained during the specified time period L ) and the maximum torque. The torque reaching M L +0.5(M H -M L ) value (t¢50) and the torque reaches M L +0.9(M H -M L ) time, and the value of the tan d curve at maximum torque (tan d M H). The results are reported in Table 3.

[0104] O-rings (214, AMS AS568) were molded at 177°C for 15 min. The press-cured O-rings were post-cured using a temperature ramp from room temperature to 150°C in 2 h and held at 150°C for 7 h, followed by a temperature ramp to 300°C in 2 h and held at 300°C for 2 h, and finally a temperature ramp to 320°C in 15 min and held for 15 min. The compression set resistance of the post-cured O-rings was tested at 300°C, 325°C, and 335°C for 70 h at an initial deflection of 25% according to ASTM D 395-03 Method B and ASTM D1414-94. The results are reported in percentage in Table 4.

[0105] Table 2. Composition

[0106]

[0107] Table 3. Characterization

[0108]

[0109] Table 4. Compression set, %

[0110]

[0111] Without departing from the scope and spirit of the present invention, foreseeable modifications and changes of the present invention will be apparent to those skilled in the art. The present invention should not be limited to the embodiments shown in this application for illustrative purposes. If there is any conflict or contradiction between the disclosure in this specification written and any document incorporated herein by reference, then the written specification will prevail.

Claims

1. A composition comprising (i) an uncured highly fluorinated elastomer comprising nitrile groups, wherein at least 80 mol % of the hydrogen atoms of the polymer backbone of the highly fluorinated elastomer have been substituted with fluorine atoms; (ii) an ammonium hydroxybenzoate compound according to the formula wherein each R1 group is independently selected from the group consisting of: H, OH, R and OR, provided that at least one R1 group is OH, and wherein R is an alkyl group; and (iii) Compounds of formula (II): Where X 1 and X 2 is independently selected from the group consisting of: O and S, and L comprises at least one multivalent phenyl group.

2. The composition according to claim 1, wherein only one R1 group is OH.

3. The composition according to claim 2, wherein the ammonium hydroxybenzoate compound is wherein each R1 group is independently selected from the group consisting of: H, R and OR, wherein each R group is independently selected from an alkyl group or an alkoxy group.

4. The composition according to claim 2, wherein the ammonium hydroxybenzoate compound is wherein each R1 group is independently selected from the group consisting of: H, R and OR, wherein each R group is independently selected from an alkyl group or an alkoxy group.

5. A composition according to claim 3 or 4, wherein each R1 group is H.

6. The composition according to claim 4, wherein the ammonium hydroxybenzoate compound is wherein each R1 group is H, and R3 is a C1 to C4 alkyl group.

7. The composition according to claim 1, wherein the ammonium hydroxybenzoate compound is wherein each R1 group is H.

8. The composition of any one of the preceding claims, wherein at least 95 mol % of the hydrogen atoms of the polymer backbone of the uncured highly fluorinated amorphous polymer have been substituted with fluorine atoms.

9. The composition of any one of the preceding claims, wherein the uncured highly fluorinated amorphous polymer comprises repeating units derived from a perfluorinated monomer comprising nitrile groups, tetrafluoroethylene (TFE) and at least one comonomer selected from the group consisting of perfluoroalkyl vinyl ether (PAVE) and perfluoroalkyl allyl ether (PAAE).

10. The composition of any one of the preceding claims, wherein the uncured highly fluorinated amorphous polymer comprises at least 1 mol% and no more than 5 mol% nitrile groups.

11. The composition of any one of the preceding claims, wherein the composition comprises at least 0.05 wt% to at most 5 wt% catalyst.

12. A composition according to any one of the preceding claims, wherein the composition comprises at least 0.05 wt% to at most 9 wt% of a compound according to formula (II).

13. The composition according to any one of the preceding claims, wherein L is a divalent group, a trivalent group or a tetravalent group.

14. A composition according to any one of the preceding claims, wherein L is or Where R 1 is selected from the group consisting of a methyl group, a methoxy group, an ethyl group and an ethoxy group, and R 2 Selected from the group consisting of a methyl group, a methoxy group, an ethyl group and an ethoxy group.

15. A composition according to any one of claims 1 to 13, wherein L is as well as Where R 4 selected from the group consisting of: a bond, -S-, -O-, -C(CF3)2-, -C(CH3)2-, -CH2-, -SO2-, -C(=O)-, and -C(CH3)2-C6H4-C(CH3)2-; each R 1 is independently selected from the group consisting of a methyl group, a methoxy group, an ethyl group and an ethoxy group, and each R 2 Independently selected from the group consisting of a methyl group, a methoxy group, an ethyl group and an ethoxy group.

16. The composition of any one of the preceding claims, wherein the composition further comprises a filler, optionally wherein the filler is at least one of carbon black or polytetrafluoroethylene or PFA.

17. An article comprising a cured elastomer derived from the composition of any one of claims 1 to 16.

18. The article of claim 17, wherein the article has a compression set of no greater than 80% after 70 hours at 335°C.

19. A method for preparing a highly fluorinated elastomer, the method comprising: The following are combined to form a mixture: (i) a highly fluorinated amorphous polymer comprising nitrile groups, wherein at least 80 mole percent of the hydrogen atoms of the polymer backbone of the highly fluorinated amorphous polymer have been replaced by fluorine atoms; (ii) an ammonium hydroxybenzoate compound according to the formula wherein each R1 group is independently selected from the group consisting of: H, OH, R and OR, provided that at least one R1 group is OH, and wherein R is an alkyl group; and (iii) an additive comprising a compound of formula (II) Where X 1 and X 2 is independently selected from O or S, and L comprises at least one multivalent six-membered aromatic hydrocarbon group.

20. The method according to claim 19, further comprising (b) molding the article at a temperature suitable for pressurized curing to form a molded article; and (c) contacting the molded article with a non-isothermal thermal cycle.

21. The method of claim 19, wherein the non-isothermal thermal cycle comprises a final ramp to a temperature of at least 300°C in less than 1 hour.

22. Use of a catalyst and an additive for curing a highly fluorinated amorphous polymer comprising nitrile groups, wherein at least 80 mol % of the hydrogen atoms of the polymer backbone of the highly fluorinated amorphous polymer have been substituted by fluorine atoms; the catalyst comprising an ammonium hydroxybenzoate compound according to the formula wherein each R1 group is independently selected from the group consisting of: H, OH, R and OR, provided that at least one R1 group is OH, and wherein R is an alkyl group; and The additive comprises a compound of formula (II) Where X 1 and X 2 is independently selected from O or S, and L comprises at least one multivalent six-membered aromatic hydrocarbon group.